Policing toxic masculinities and dealing with sexual violence on Zimbabwean University campuses - Gukurume, Simbarashe (HTS teologiese studies, 2023)
University campuses are framed as sexualised spaces marked by high sexual risk-taking behaviour and toxic masculinities that often fuel abusive relationships and sexual violence. More often, the most vulnerable groups, to this violence include sexual minorities, girls and students with disabilities. Drawing on qualitative ethnographic research and semi-structured interviews with students and staff from two universities in Zimbabwe, this article examines how toxic campus ‘cultures’ and campus sexual economies can be transformed and made more inclusive and safer for all students. The study uses Pierre Bourdieu’s theory of practice, especially the field and habitus to understand how toxic masculinities are produced and reproduced on campus, as well as how everyday practice on campus can be instrumentalised to reconfigure coercive sexual practices and toxic masculinities. Although there is a huge body of research on sexual violence in Zimbabwe, very little of this has focused on the prevalence and experiences of this phenomenon within university campus spaces. Therefore, little is known about how students experience, perceive, and navigate sexual violence on campus, as well as institutional responses to sexual violence. Consequently, this study seeks to fill this gap and contribute to the burgeoning scholarship and debates on sexual violence, including coercive sexual practices and heteronormativity in university campus spaces. We seek to contribute to three sustainable development goals, that is goal 3 (good health and well-being), goal 5 (gender quality) and finally goal 10 (reduced inequalities).Contribution: This article foregrounds the ways in which institutions of higher learning respond to sexual violence within the university campus. The key contribution of this article relates to how students’ religious and socio-cultural subjectivities shaped or mediated experiences of and perceptions on sexual violence on campus. Consequently, we assert that the campus religious ‘field’ and students’ spiritual ‘habitus’ had a huge influence on the campus sexual economies.The research contributes to the field of Biblical Theology engaged with Gender Justice, Health and Human Development.